Sensitivity Testing of Simple Metal Detection System on Coil Dimension Change and Measurement Distance - Bangun, Abel Melido; Yuliza, Elfi; Ekawita, Riska (JPSE (Journal of Physical Science and Engineering), 2023)
Metal residues in the soil at shallow depths can be detected with simple detectors. Development was carried out using several equipment tests. The purpose of this research is to design a simple metal detection system by testing the coil diameter, the wire diameter, and the number of coil windings to determine their effect on the detection distance of the metal detection system. The metal detection system in this study uses the pulse induction method, which uses one coil as a transmitter and receiver. The wire used 4 types of diameter sizes. For one size of wire diameter, three variations of the number of coil windings are made, and for each variation of the number of coil windings, five variations of coil diameter are made. The test results show that the diameter of the coil affects the detection distance of a simple metal detection system, the larger the diameter of the coil, the farther the detection distance for medium and large-sized metals, while for small metals, the lower the detection distance. Wire diameter affects the detection distance of a simple metal detection system, the larger the wire diameter, the farther the detection distance, and vice versa, the smaller the wire diameter, the lower the detection distance. The number of coil windings affects the detection distance of a simple metal detection system, the more turns, the farther the detection distance, while the fewer turns, the closer the detection distance.